The Influence of Workload, Reward and Punishment, and Work Environment on Employee Performance at RSUD dr. H. Koesnadi Bondowoso through Work Motivation as an Intervening Variable - Doni Prianto; Yuniorita Indah Handayani; Diana Dwi Astuti (Medikun Publisher, 2024)
This study analyzes the influence of workload, reward and punishment, and work environment on employee performance at RSUD dr. H. Koesnadi Bondowoso, with work motivation as an intervening variable. Using a quantitative approach and path analysis, the study examines direct and indirect effects among variables. The population comprises non-medical employees, with a sample determined using the Slovin formula and selected via stratified random sampling. The results indicate that workload, reward and punishment, and work environment significantly affect employee performance. These factors also influence work motivation, which in turn positively impacts performance. Motivation serves as a partial mediator, highlighting its critical role in linking workload, reward and punishment, and work environment to employee performance. The study emphasizes the importance of optimizing workload allocation, implementing fair reward and punishment systems, and fostering a conducive work environment. Enhancing employee motivation is essential for maximizing the impact of these factors on performance. The findings offer valuable insights for management at RSUD dr. H. Koesnadi Bondowoso and contribute to human resource management knowledge in the healthcare sector. Addressing these elements holistically can significantly improve employee performance and support the development of effective policies for organizational efficiency and employee well-being